2022
DOI: 10.3390/diagnostics12040921
|View full text |Cite
|
Sign up to set email alerts
|

MRI Evaluation of Complete and Near-Complete Response after Neoadjuvant Therapy in Patients with Locally Advanced Rectal Cancer

Abstract: Purpose To evaluate MRI performance in restaging locally advanced rectal cancers (LARC) after neoadjuvant chemoradiotherapy (nCRT) and interobserver agreement in identifying complete response (CR) and near-complete response (nCR). Methods 40 patients with CR and nCR on restaging MRI, surgery and/or endoscopy were enrolled. Two radiologists independently scored the restaging MRI and reported the presence of split scar sign (SSS) and MRI tumor regression grade (mrTRG). Diagnostic accuracy and ROC curves were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The initial search yielded 3015 articles (Fig. 2 ), from which 71 articles were reviewed, and 4 articles were considered eligible [ 3 , 9 11 ]. Three of the studies were retrospective; of these, two were single-center and one was multi-center.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial search yielded 3015 articles (Fig. 2 ), from which 71 articles were reviewed, and 4 articles were considered eligible [ 3 , 9 11 ]. Three of the studies were retrospective; of these, two were single-center and one was multi-center.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the studies employed rectal microenema, while the other study did not provide this information. Two authors justified the use of microenema to reduce DWI susceptibility artifacts [ 9 , 11 ]. Although it is not a consensus, this approach is aligned with evidence provided by a small sample single-center study that reported better quality in DWI with reduced geometric distortion from rectal gas [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RT and/or CT are often used to treat LARC, followed by total excision of the mesorectum (4)(5)(6)(7). This treatment approach has been shown to reduce tumour size and stage, and can result in a pathological complete response in 10% to 25% of patients (6,8,9). Patients who have achieved a complete response after NAT can benefit from less invasive treatment options, such as local resection with anal sphincter sparing and the nonsurgical approach after NAT known as Watch and Wait (6,8,(10)(11)(12).…”
Section: Introduction Introductionmentioning
confidence: 99%
“…However, no consensus exists for any reliable and reproducible methods for accurate prediction before operation. The mrTRG, proposed by the MERCURY research team ( 11 ), was demonstrated in several studies ( 10 , 12 , 13 ) to have a significant association with pCR, while a recent meta-analysis reported that mrTRG exhibited superior specificity (93.5%) for pCR, but inferior sensitivity (32.3%) ( 14 ).…”
Section: Introductionmentioning
confidence: 99%